Work–Family Policy Trade-Offs for Mothers? Unpacking the Cross-National Variation in Motherhood Earnings Penalties. (May 2016) - Budig, Michelle J.; Misra, Joya; Boeckmann, Irene
Recent scholarship suggests welfare state interventions, as measured by policy indices, create gendered trade-offs wherein reduced work–family conflict corresponds to greater gender wage inequality. The authors reconsider these trade-offs by unpacking these indices and examining specific policy relationships with motherhood-based wage inequality to consider how different policies have different effects. Using original policy data and Luxembourg Income Study microdata, multilevel models across 22 countries examine the relationships among country-level family policies, tax policies, and the motherhood wage penalty. The authors find policies that maintain maternal labor market attachment through moderate-length leaves, publicly funded childcare, lower marginal tax rates on second earners, and paternity leave are correlated with smaller motherhood wage penalties.